Diagnostic value of biomarkers for paediatric urinary tract infections in primary care: systematic review and meta-analysis - Hanne A. Boon; Thomas Struyf; Dominique Bullens; Ann Van den Bruel; Jan Y. Verbakel (BMC Family Practice, 2021)
Abstract Background Accurate diagnosis of urinary tract infection is essential as children left untreated may suffer permanent renal injury. Aim To compare the diagnostic values of biomarkers or clinical prediction rules for urinary tract infections in children presenting to ambulatory care. Design and setting Systematic review and meta-analysis of ambulatory care studies. Methods Medline, Embase, WOS, CINAHL, Cochrane library, HTA and DARE were searched until 21 May 2021. We included diagnostic studies on urine or blood biomarkers for cystitis or pyelonephritis in children below 18 years of age. We calculated sensitivity, specificity and likelihood ratios. Data were pooled using a bivariate random effects model and a Hierarchical Summary Receiver Operating Characteristic analysis. Results Seventy-five moderate to high quality studies were included in this review and 54 articles in the meta-analyses. The area under the receiver-operating-characteristics curve to diagnose cystitis was 0.75 (95%CI 0.62 to 0.83, n = 9) for C-reactive protein, 0.71 (95% CI 0.62 to 0.80, n = 4) for procalcitonin, 0.93 (95% CI 0.91 to 0.96, n = 22) for the dipstick test (nitrite or leukocyte esterase ≥trace), 0.94 (95% CI 0.58 to 0.98, n = 9) for urine white blood cells and 0.98 (95% CI 0.92 to 0.99, n = 12) for Gram-stained bacteria. For pyelonephritis, C-reactive protein < 20 mg/l had LR- of 0.10 (95%CI 0.04–0.30) to 0.22 (95%CI 0.09–0.54) in children with signs suggestive of urinary tract infection. Conclusions Clinical prediction rules including the dipstick test biomarkers can support family physicians while awaiting urine culture results. CRP and PCT have low accuracy for cystitis, but might be useful for pyelonephritis.